PENERAPAN NILAI DAN NORMA KEDISIPLINAN SEKOLAH DASAR ISLAM TERPADU AL-MADINAH PONTIANAK - Yusni Ramdhani; Rustiyarso Rustiyarso; Supriadi Supriadi (ICoTE Proceedings, 2019)
This study aims to find out and obtain information about the application of value and discipline norm at SDIT Al-Madinah Pontianak. The approach used is qualitative research with descriptive research methods. The results showed that the application of value and discipline norm at SDIT Al-Madinah Pontianak had been carried out well, among others: discipline of students to not be late for school, neatness of students in dressing, students attending Dhuhr prayer together, and taking extracurricular activities according to provisions school. Constraints faced lies in the students themselves because of the lack of discipline of students in managing themselves in the enforcement of the rules, so that there are still students who have not been able to discipline for themselves to comply with the Rules set by the school.